Implementasi Blockchain berbasis BigchainDB untuk Menjamin Keamanan Data dalam Sistem Pencatatan Rekam Medis - Jogi Oliver Yohanes Tampubolon; Adhitya Bhawiyuga; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Increasing interest on digitalization of medical records and also the occurrence of a pandemic, pushes the increase usage of the Electronic Health Record (EHR) system by the health service providers. However, large amount of these systems still implements the centralized architecture that may pose risks such as data corruption, privacy infringement, and limited performance. Hence, blockchain technology are being researched as a substitute to handle data on EHR systems due to its decentralized architecture. The blockchain framework that is being researched in this report is BigchainDB, due to its capabilities on managing large-sized data similar to a conventional database. BigchainDB inherits the blockchain characteristics by also having a decentralized architecture, which means it can communicate its peers by using a peer-to-peer connection. BigchainDB also uses a consensus algorithm for transaction verification. BigchainDB consists of three main components; the â€œBigchainDB serverâ€, which responsible for transaction handling from the web server to the blockchain, â€œTendermintâ€, which responsible for the blockchain protocol and peer-to-peer communication, and â€œMongoDB", which responsible for the data storage. The BigchainDB also have data ownership control through the Role Based Access Control (RBAC) feature, which is a subsystem that allows the formation of data hierarchy that consists of roles and permissions for every transaction.